(untitled) (Acta Scientiarum. Biological Sciences, 2023)
Species of the genus Pimelodella (Eigenmann & Eigenmann, 1988) present many similar morphological characteristics, which makes taxonomic identification difficult. Some species present morphological distinction and reproduce normally, while others present reproductive isolation without morphological distinction. Taking that into consideration, we used starch-gel electrophoresis of enzymes to compare two species of the genus Pimelodella collected in Paraná, Ivaí and Pirapó rivers of the Upper Paraná River basin. We analyzed the liver and muscle tissue of 82 Pimelodella avanhandavae and 29 Pimelodella gracilis individuals, which revealed few genetic differences between species. In addition, we carried out an experimental design based on the separation of four populations: P. avanhandavae, Parana River (n = 37); P. avanhandavae, Ivaí River (n = 6); P. gracilis, Ivaí River (n = 29); P. avanhandavae, Pirapó River (n = 39). The high proportions of polymorphic loci as well as the expected heterozygosity suggest that both species have high genetic variability. Nei’s genetic identity values and Wright’s fixation indices revealed a large genetic proximity between the samples collected in Ivaí and Pirapó rivers, regardless of the species analyzed. The presence of fixed alleles at one hundred percent for two loci showed that P. avanhandavae individuals collected in the Parana River are genetically distant from all remaining populations. Data indicated that P. avanhandavae, collected in this river, constitutes a distinguished species from those collected in Ivaí and Pirapó rivers. Therefore, we suggest, that more studies with molecular markers be carried out with the genus, as well as a review of the diagnostic morphological characteristics used to separate P. avanhandavae from P. gracilis.